PENINGKATAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MEDIA BANGUN DATAR SEDERHANA DI KELAS I SEKOLAH DASAR - Rusmiati, Rusmiati; Kartono, Kartono; Margiati, Margiati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe simple flat building media that can improve the mathematics learning outcomes of first grade students of Negeri 21 Rantau Sibaju Bengkayang Elementary School. Data collection techniques used are observation techniques and measurement techniques with data collection instruments namely observation and test sheets. The results of the study of the implementation of learning design (RPP) from cycle I to cycle III get an average score of 3.67 in the excellent category. The results of the study of the implementation of learning from the first cycle average score of 2.81, cycle II an average score of 3.51 and the third cycle average score of 3.94, always experiencing an increase due to the implementation of learning using the media to build flat teachers always do improvements in each cycle. The results of student learning from the first cycle average value of 55.09, cycle II an average value of 71.76 and cycle III an average value of 81.94. Based on the data obtained it can be concluded that there is an increase in each cycle Thus the research using simple flat-build media on learning to know class I flat build can improve student learning outcomes. Keywords: Flat Build Media, learning outcomes, mathematics.